PENGUATAN KOMPETENSI PROFESIONAL GURU BAHASA INDONESIA DALAM MENGHADAPI BERBAGAI FENOMENA KEBAHASAAN DI ERA DIGITAL - Fadlilah, Afi; Saifullah, Aceng Ruhendi; Anshori, Dadang; Idris, Nuny Sulistiany; Nugroho, Rudi Adi (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2021)
Today's language and technology have presented various linguistic phenomena in society, both in real and virtual or virtual spaces. Indonesian language teachers really need to keep up with language developments in an increasingly sophisticated digital era. Indonesian language learning in schools needs to be linked to language phenomena that occur in society. This community service activity aims to strengthen the linguistic competence of Indonesian language teachers in dealing with various language phenomena in the digital era. This activity is carried out in the form of online seminars and workshops using the Zoom media. This activity involved Indonesian language teachers who were members of the Junior and Senior High School Subject Teacher Consultative Forum (MGMP) in Kuningan Regency. The results obtained from this service are an increase in the understanding and competence of the participants regarding aspects of the Indonesian language in the digital era. The participants became more aware of various current linguistic phenomena, especially Indonesian which can be taken into account in formulating Indonesian language learning in schools. Although the activities were conducted online, all participants gave positive responses to this activity.